Musikermobilitet i Østersøområdet i 1600- og 1700-tallet - Koudal, Jens Henrik; Harwell, Anna H. (Danish Yearbook of Musicology, 1994)
The Mobility af Musicians in the Baltic Area in the Seventeenth and Eighteenth Centuries This article is a supplement to the discussion of Baltic Music Culture ("Die Musikkultur des Ostseeraumes") – a concept introduced by Carl Allan Moberg in 1957. Eight German-texted passport ledgers preserved in Denmark have served as valuable source materials for examining the mobility of musicians in the 17th century. Used by the military, these ledgers kept track of persons travelling in and out of Copenhagen from 1663 to 1669 and in 1671. Each ledger entry is dated and records the individual's name, occupation, destination and/or place of departure. Approximately 225 different musicians appear in these ledgers (their personal information appears in the appendix of this article). The information attained from the ledgers reveals that musicians were divided into three general categories: Trompeter, Organist or Musikant, and that the most common place of travel was the Baltic area: Denmark-Norway, Sweden and the commerce cities of Northern Germany (from Königsberg in the East to Bremen in the West). The social milieu in the Baltic area is reflected by the musicians in these records – court musicians, city musicians, organists, military musicians and special musicians whose territory was limited to rural areas. Comparisons are made between the seventeenth-century ledgers and Copenhagen's passport ledgers from 1788-1790. Also discussed are the critical source problems associated with the use of passport information. Finally the mobility of musicians is discussed specifically, and it is concluded that the dominant direction of movement was from south to north, from Germany to Denmark-Norway and Sweden. Although there was some movement between Denmark and the old Danish provinces in Sweden, Danish-Norwegian and Swedish musicians primarily worked in their own respective countries. In general, mobility was greater in the 1600s than in the 1700S. The courts attracted Italian, French, English and German musicians, but for the most part it was only the Germans who settled in the North and whose descendents remained there. City musicians in Denmark-Norway held permanent offices, whereas the more prestigious organists and trumpeters shifted between various appointments. While the courts oriented themselves towards the rest of Europe, the cities oriented themselves more locally to the Baltic region. Although political situations in the Baltic area had some effect on the mobility of musicians, economic and social circumstances carried the greatest influence. In Denmark city musicians and peasants shared a close relationship, however, the general social movement of musicians tended to flow from the military and court levels to the civic level.